Penggunaan Media TIK untuk Meningkatkan Prestasi Belajar Siswa pada Pembelajaran Al-Quran di SDN 6 Mataram - Mustaqim Mustaqim (Jurnal Paedagogy, 2020)
The purpose of this study is to improve student achievement through the use of ICT media in learning the Qur'an in class IV SDN 6 Mataram. This study uses a class action research method which consists of 4 stages, namely planning, action implementation, observation and reflection. The research instruments used were observation sheets and tests. While the technical analysis of the data of this study uses descriptive qualitative and qualitative analysis techniques. The results of this study concluded that (1) problem-based learning has a positive impact in improving student achievement which is marked by an increase in student learning completeness in each cycle, namely cycle I (58.33%), cycle II (77.77%), cycle III (88.88%). (2) The use of ICT media in learning the Qur'an has a positive effect, which can improve student achievement shown by the results of observations of students during the learning process.